Exploring socio-economic externalities of development scenarios. An analysis of EU regions from 2008 to 2016. (15th April 2023) - Mura, Matteo; Longo, Mariolina; Zanni, Sara; Toschi, Laura
Abstract: A great debate around development scenarios has come to define conversations around the economy and the environment, two dimensions that struggle to find a proper balance. In this paper we apply unconditional growth model analyses to a new and unique dataset of European regions between 2008 and 2016 and identify four development scenarios – green growth, green de-growth, black growth and black de-growth – characterized by different relationships between CO2 emissions and economic growth. We then map European regions across these four scenarios and describe the differences that occurred among regions in terms of socio-economic externalities, mainly competences, investments and well-being. Drawing on our analyses, we contribute to the debate on development scenarios and ecological macro-economics, as well as discuss implications for sustainability policy and research. Highlights: Industrial transition is characterised by environmental and socio-economic factors. EU regions are clustered based on CO2 and Gross Value Added over a 9-year period. Decoupling environmental and economic components defines four development scenarios. Socio-economic effects of transition are tested by unconditional growth modelling. Competences result a key feature for developing absolute decoupling scenarios.